2019
DOI: 10.23818/limn.38.25
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic, functional and phylogenetic diversity: how subfossil cladocerans mirror contemporary community for ecosystem functioning: a comparative study in two oxbows

Abstract: Taxonomic, functional and phylogenetic diversity: how subfossil cladocerans mirror contemporary community for ecosystem functioning: a comparative study in two oxbowsBiases of taxa diversity and traits of source (active) and subfossil cladoceran communities with phylogenetic and functional approach were studied in two oxbows of the River Tisza, Hungary. Subfossil cladoceran communities were found to have suffered species loss due to both the degree of heterogeneity in the lake and taphonomical processes. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…A subfossil assemblage's diversity and density come from several years' deposition in the surface sediment as well as its connection with environmental variables [17,48]. Korponai et al [49] reported that 27 taxa for contemporary and 18 taxa for subfossil Cladocera species were determined in the same region. These differences are probably due to differences in the sampling points; indeed, Korponai et al used one sampling point from each oxbow lake while we collected samples from 21 different points.…”
Section: Discussionmentioning
confidence: 99%
“…A subfossil assemblage's diversity and density come from several years' deposition in the surface sediment as well as its connection with environmental variables [17,48]. Korponai et al [49] reported that 27 taxa for contemporary and 18 taxa for subfossil Cladocera species were determined in the same region. These differences are probably due to differences in the sampling points; indeed, Korponai et al used one sampling point from each oxbow lake while we collected samples from 21 different points.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying changes in zooplankton communities (individual size, biomass, population, community structure, etc.) within lake ecosystems is an important task for effective lake management [29,30].…”
Section: The Role Of Zooplankton In Lake Ecosystemsmentioning
confidence: 99%
“…They are regarded as a model group for ecology, evolution, and toxicology [22,23], and as indicators of water quality [24], the tropic status of lakes [25], fish pressure on planktonic communities [26], etc. Their remains are well-preserved in the lake bottom sedinents, and they are widely applied in the paleoecological reconstructions [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%